FORMATION OF THE HUMAN CAPITAL MANAGEMENT SUBSYSTEM OF THE ENTERPRISE ORIENTATION ORIENTATION - Mаtskevуch, O. Y. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
Increased influence of human capital on the development of economic entities leads to the existence of an urgent need to develop an adaptive to modern conditions methodology for evaluating the effectiveness of the company's human capital management subsystem. The article mentions the necessity of human capital management in the context of ensuring strategic development of the enterprise. The author substantiates that human capital is a strategic potential, an inexhaustible reserve for improving the company's efficiency in an innovative economy, which affects its competitiveness, determines the directions for further development. The emphasis is placed on the fact that high results of company's effective human capital management can be achieved under the condition of continuous analysis of human capital state, which has a direct connection with company's overall effective activity parameters. The preconditions for the implementation, the purpose and the main objectives of company's human capital management are established. Human capital management is considered as a dynamic set of interrelated administrative processes: the formation, development, realization and reproduction of human capital. The author's approach to the estimation of company's human capital management subsystem efficiency is proposed. According to this approach, the key criteria for assessing the efficiency of company's human capital management are defined as effectiveness, efficiency and profitability. It is noted that the complex assessment of the human capital management subsystem ensures the company's uninterrupted feedback and is a powerful lever for increasing the efficiency of the management processes. The author describes the relevant indicators for assessing the performance level of the human capital management subsystem according to the determined criteria.